2018
DOI: 10.1007/s13730-018-0308-3
|View full text |Cite
|
Sign up to set email alerts
|

Renal medullary carcinoma: a nearly fatal malignancy specifically affecting patients with a so-called benign condition

Abstract: Renal medullary carcinoma (RMC) is a highly aggressive and rare malignancy found almost exclusively in young patients with sickle cell trait (SCT). Metastatic disease is commonly present at diagnosis. There is very limited experience treating disseminated disease and the prognosis is dismal. We report the case of a young 9-year-old boy with SCT, who presented with 4 months' progression of abdominal pain, nausea and vomiting associated with cough spells, dysphagia, and weight loss. Upon evaluation, he was under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…To date, platinum-based chemotherapy is the recommended initial standard of care for patients diagnosed with RMC, given the rapid progression that can be seen in these patients [42]. This includes high-dose intensity MVAC (a combination of methotrexate, vinblastine, doxorubicin, and cisplatin) [28,43] and PCG (paclitaxel, cisplatin or carboplatin, and gemcitabine) [44][45][46], which are regimens used in urothelial carcinoma [47]. Following upfront chemotherapy, surgery is considered-particularly for those who have responded to chemotherapy.…”
Section: Therapeutic Considerations From Biologymentioning
confidence: 99%
“…To date, platinum-based chemotherapy is the recommended initial standard of care for patients diagnosed with RMC, given the rapid progression that can be seen in these patients [42]. This includes high-dose intensity MVAC (a combination of methotrexate, vinblastine, doxorubicin, and cisplatin) [28,43] and PCG (paclitaxel, cisplatin or carboplatin, and gemcitabine) [44][45][46], which are regimens used in urothelial carcinoma [47]. Following upfront chemotherapy, surgery is considered-particularly for those who have responded to chemotherapy.…”
Section: Therapeutic Considerations From Biologymentioning
confidence: 99%
“…Most people with sickle cell trait live asymptomatically. Despite SCT being perceived as an asymptomatic condition several case reports and reviews reported an increased incidence of renal medullary carcinoma among young patients with SCT with the age wide from 9 to 69 years (12)(13)(14). Other forms of SCT include HbAC, and HbAE although these are rare forms (9).…”
Section: Introductionmentioning
confidence: 99%
“…Most people with sickle cell traits live asymptomatically. Despite SCT being perceived as an asymptomatic condition, several case reports and reviews have reported an increased incidence of renal medullary carcinoma among young patients with SCT aged 9 to 69 years [12][13][14]. Other forms of traits include HbAC and HbAE, although these are rare forms [9].…”
mentioning
confidence: 99%